Characterizing composition profile and diversity patterns of spontaneous urban plants across China's major cities. (1st September 2022) - Hu, Siwei; Jin, Cheng; Huang, Li; Huang, Junlong; Luo, Min; Qian, Shenhua; Jim, C.Y.; Song, Kun; Chen, Shengbin; Lin, Dunmei; Zhao, Liang; Yang, Yongchuan
Abstract: Spontaneous urban plants (SUPs) constitute an important component of urban vegetation, but they have received less attention in urban biodiversity and ecological research, especially at the regional scale. We comprehensively reviewed the occurrence records of SUPs in 59 major cities across China's geographical regions. We systematically analyzed floristic composition profiles and diversity patterns of SUPs at the regional scale and explored their influencing factors. The study identified 1211 SUP species through an extensive search of existing field research studies and fieldwork. The species composition pattern of SUPs, displaying a spatial association with climatic zones, was mainly affected by climatic factors and also anthropogenic factors. At different geographic scales, the life-form characteristics revealed some patterns, with more diverse perennials at the regional scale. The abundance of SUPs and the high proportion of native species suggested that limited urban habitats can still contribute to the enrichment and accumulation of urban biodiversity. However, in the context of globalization, continual species exchanges between neighboring regions at different scales may significantly exacerbate urban-biota homogenization. In conclusion, our study provided a regional-scale case of a synoptic SUP profile. The results furnished a scientific basis for understanding the general patterns of SUPs. The findings could inform sustainable solutions for urban ecological planning and management of spontaneous nature in cities. Highlights: 1211 spontaneous urban plant (SUP) species were recorded in 59 China's major cities. Besides climatic factors, SUPs composition significantly correlated with city's GDP. Species exchange between neighboring regions accelerated homogenization. SUPs can be applied to urban rewilding and biodiversity enhancement endeavors.